Switching Enantioface Selection in the Asymmetric Nitro-Mannich Reaction Using Single Chiral Bis(imidazolidine)pyridine–Metal Catalysts - Arai, Takayoshi; Matsumura, Eri (Synlett, 2014)
Switching enantioface selection of imines in the metal-catalyzed nitro-Mannich reaction was accomplished with the same enantiomer of diamine-derived bis(imidazolidine)pyridine (PyBidine) ligand. The (S,S)-PyBidine–CoCl2 complex catalyzed the nitro-Mannich reaction of N-Ts imines to give S-enriched adducts, while the Ni(OAc)2 complex using the same ligand catalyzed the nitro-Mannich reaction of N-Boc imines in an R-stereoselective manner.
Keywords: asymmetric catalysis; chirality; nitro-Mannich; imines; metal salts